A 19. század végi agrárválság hatásai a Dél-dunántúli régió uradalmi gazdálkodására - Kaposi, Zoltán (Közép-Európai Közlemények, 2015)
Despite the previous development the domestic agrarian sector experienced a recession for one and half decade from the 1880s. This had two reasons. First, effects of depressed prices in the world economy touched Hungary too; second, due to the phylloxera epidemic wine production crisis occurred. In this study we examine the responses given to the crisis, mostly focusing on the South Transdanubian region. We point out that large scale agrarian plants tried to mitigate the situation in many ways. Instead of the previous grain production they increased the intensive farming which enabled the acclimatisation of many new plants. Mechanisation developed too. More plants were grown for industrial processing (mainly sugar beets). With the acclimatisation of new species the husbandry was modernised and indoor farming spread quickly. Many large estates moved toward high quality forestry. Leasing of the large estates resulted new capital flowing to the agrarian sector. Tendency for creating co-operatives strengthened. Due to these changes in the beginning of the 20th century we can observe a more intensively and flexibly working manorial management.